Reconceptualising education support services in South Africa - Hay, Johnnie (AOSIS, 2021)
Inclusive education has been phased in in South Africa since 2001, but relies heavily upon adequate support services to support learners and teachers experiencing barriers to learning and development. This book focuses on the different levels of support provided in South African education - from School-based Support Teams to District-based Support Teams through to special and full-service schools, and how these could be reconceptualised to provide improved support to learners and teachers. Current research indicates that inclusive education is being implemented in varied and fragmented forms across the country, and the point of departure of this work is that education support services need to be improved and reconceptualised to ensure better support for inclusive education.